1997
DOI: 10.4141/a95-125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fish oil and monensin on milk composition in dairy cows

Abstract: Cant, J. P., Fredeen, A. H., MacIntyre, T. Gunn, J. and Crowe, N. 1997. Effect of fish oil and monensin on milk composition in dairy cows. Can. J. Anim. Sci. 77: 125-131. Four primparous Holstein cows were used in a 4 × 4 Latin square with 21-d periods to determine the effect of redfish oil and monensin sodium on milk composition. The four dietary treatments were a basal diet (control), the basal diet plus 14.5 mg monensin kg -1 dietary dry matter (M), 2% fish oil (FO), and a combination of fish oil and monens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
47
5
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 38 publications
(52 reference statements)
18
47
5
1
Order By: Relevance
“…The fish meal supplement linearly increased milk (22.9, 25.7, 26.5 kg d -1 , SE 1.12), protein, and lactose yields (P < 0.05; Wright et al 1998); however, there were linear declines (P < 0.01) in both milk fat yield (0.78, 0.71, and 0.62 kg d -1 , SE 0.03; Wright et al 1998) and content (3.35, 2.74, 2.38 g (100 g) -1 , SE 0.11) as supplementation increased from low to high, respectively. These data agree with literature that indicates the level of milk fat depression is dependent on the level of unprotected fish oil (present in fish meal) fed (Cant et al 1997).…”
supporting
confidence: 82%
“…The fish meal supplement linearly increased milk (22.9, 25.7, 26.5 kg d -1 , SE 1.12), protein, and lactose yields (P < 0.05; Wright et al 1998); however, there were linear declines (P < 0.01) in both milk fat yield (0.78, 0.71, and 0.62 kg d -1 , SE 0.03; Wright et al 1998) and content (3.35, 2.74, 2.38 g (100 g) -1 , SE 0.11) as supplementation increased from low to high, respectively. These data agree with literature that indicates the level of milk fat depression is dependent on the level of unprotected fish oil (present in fish meal) fed (Cant et al 1997).…”
supporting
confidence: 82%
“…However, the present results indicated that fish oil had no negative effect on DM intake. Unlike to the present study, this is because silage and concentrate were fed separately so the reduction in ad libitum silage intake by addition of fish oil to the concentrate suggests a more general effect on feed consumption in the work of Cant et al(1997). While all nutrients flow to the duodenum, and digestion in the rumen and total tract were not significantly different among the treatments.…”
Section: Resultscontrasting
confidence: 47%
“…Other researchers have also reported a decrease in DM intake of dietary source when cows are infused with unsaturated fat (Bremmer et al, 1998). In addition, Cant et al (1997) observed that a decreased 10% in DM intake was noted when the fish oil diets were fed because the diets had a fish odour which may have reduced cow's palatability. However, the present results indicated that fish oil had no negative effect on DM intake.…”
Section: Resultsmentioning
confidence: 99%
“…This may have been a consequence of greater ruminal biohydrogenation and/or a poorer efficiency of absorption. While the majority of studies have shown a greater rate of transfer from diet to milk for DHA compared with EPA (Cant et al, 1997;Mattos et al, 2004), a recent study from our laboratory has shown EPA to be transferred more efficiently to a number of key reproductive tissues including uterine endometrium and follicular fluid .…”
Section: Discussionmentioning
confidence: 99%